Autorregulamentação coletiva e jurisdição como fontes do direito do trabalho : o problema da aderência das normas coletivas nos contratos individuais de trabalho - Mies, Natalia Schnaider Serro (2015)
This study describes collective bargaining and case law as sources of Labor Law, analyzing their characteristics, limitations and effects concerning individual employment contracts. Finally, the intention of this study was of analyzing all of these matters under the terms of the new text of Precedent 277 of the Superior Labor Court pursuant the concept of applicability after abrogation. The study first examined collective self-regulation, its concept, background, characteristics and, specifically, its two instruments of concretion, which are collective-bargaining agreements and collective labor agreements. The second part of the study explored case law as a source of Labor Law, it being contemplated in manner of collective labor disputes and the normative power of Labor Courts that presents itself by means of judicial disposition of collective labor grievances. As to reach the final purpose of this study, it was necessary to analyze the limits of such normative power. Finally, the concept of collective private autonomy was ascertained, as well as the problems deriving from the incorporation of collective rules to individual employment contracts. In these terms, this study undertakes, as its main purpose, to analyze the collective private autonomy and case law as sources of Labor Law rules, given their peculiarities, especially in light of the new text of Precedent 227 of the Superior Labor Court. This study elected bibliographical research as its main instrument of investigation.